DYNAMIC TEST OF SPAN STRUCTURE TYPE 690/7K - Borshchov, V. I.; Zhurbenko, M. K.; Sukhorukov, B. D. (Science and Transport Progress, 2004)
The article considers the results of dynamic tests of sectional structures, with 110m rated flight length, manufactured under standard project 690 7 К .